Home food gardens and poverty alleviation in the rural area of Macekane, KwaZulu-Natal - Lugagu, Snenhlanhla (Department of Social Development, 2025)
Access to food, water and nutrition is a constitutional right in South Africa, yet the state of food accessibility is questionable, particularly in rural communities. After South Africa achieved political freedom in 1994, development and prosperity were prioritised, and a number of policies were designed to eradicate poverty and inequalities. However, these policies have had little effect on food security, which is still precarious in many places, especially deep rural areas. This research explored the effects of home food gardens on food accessibility and poverty reduction in the rural area of Macekane in KwaZulu-Natal. It sought to investigate the circumstances of food insecurity in this area that prevail in the face of government-related food security interventions in rural areas. The focus of the research was a recent project initiated by the youth in the uMhlathuze Municipality's Ward 31, which falls under the Somopho Traditional Council. The youth initiated a ‘One home, one garden' project to address food insecurity and support self-sustainability in the community. The research employed a qualitative approach in which participants with food gardens were purposively selected and interviewed about their experiences of producing food to sustain their households. The findings revealed that water accessibility was a hindrance to the maintenance of home food gardens in Macekane. Home food gardens could contribute to the livelihood of the Macekane community, but water scarcity poses a major obstacle to achieving this goal. There is also a need for more systematic planning and implementation of community programmes such as this to ensure their success. This research brings a new perspective to the topic of food insecurity as its focus is on a specific rural community and their experiences. It therefore fills a gap in the discourse on poverty alleviation and food shortages in rural areas.